Second Method of Lyapunov for Boundedness in Terms of two Measures for Impulsive Functional Differential Systems - Stamova, I.M. (Электронное моделирование, 2008)
This paper studies an initial value problem for impulsive functional differential equations with finite delay and fixed moments of impulse effect. By using piecewise continuous functions coupled with the Razumikhin technique sufficient conditions for boundedness in terms of two different piecewise continuous measures of such equations are found. The results extend and improve the earlier publications.